A Technical Comparative Review of Energy Storage Technologies for the Future of Power Systems - Patmal, Mohammad Hamed (Journal of Natural Sciences – Kabul University, 2025)
Renewable energy is considered to be the only solution for current and future energy demands. A significant portion of renewable energy depends on solar and wind, the sources of which are beyond human control. Consequently, it is difficult to balance energy production with demand. To ensure sufficient energy during peak demand, it is necessary to develop effective energy storage technologies. This study provides a brief review of the technologies used for energy storage systems. The energy storage technologies will be evaluated from various perspectives, including technical specifications, applications, advantages, and disadvantages. Finally, a comparison of these technologies will be made, and solutions to the current issues surrounding them will be proposed.